A pollinating technique in maize (Zea mays L.) - Zainal Abidin, Mohd Idris; Banta, Michael Gregory Timfrick (Universiti Pertanian Malaysia, 1979)
In an effort to improve existing maize varieties by the simple recurrent selection procedures at the Universiti Pertanian Malaysia, Sarawak Branch Campus, we adopted the tassel bag method of hand pollination on three varieties: UPM Sweet Corn, Thai Opaque, and Mardi Composite 1. This method involves covering both the female flower (shoot) and the male flower (tassel) before the appearance of the silk and the shedding of pollen, The tassel is covered with a brown bag to collect pollen and the shoot is covered to prevent contamination from undesirable pollen. In cross-pollination, the pollen is dropped-into silk of a different plant. Pollination must be done from 10.00 to 11.30 a.m. before the pollen die. After pollination, fertilization occurs and the grain is ready to be harvested 47 - 52 days after pollination.